Impact of a structured training program to enhance skills in phacoemulsification surgery - Anuprita Gandhi Bhatt; Kuldeep S Dole; Madan Deshpande; Khurshed Bharucha; V K S Kalyani (Indian Journal of Ophthalmology, 2021)
Purpose: The aim of this study was to determine whether the introduction of a structured short-term phacoemulsification training program improved the ICO-OSCAR (International Council of Ophthalmology's Ophthalmology Surgical Competency Assessment Rubric) score and the learning curve of the trainees and decreased the complication rates of the cases. Methods: This study was a retrospective, observational study conducted in a tertiary eye care hospital in India. The study was conducted from March 2018 to October 2019 based on a structured phacoemulsification training program introduced in January 2019. The trainees enrolled in the phacoemulsification training program were divided into two groups: Group 1 (n = 33), who underwent training before the introduction of the structured program, and Group 2 (n = 29), who underwent the training after the introduction of the structured training program. Each trainee performed 20 cases. Group 1 training consisted of wet-lab and phacoemulsification surgeries. Group 2 training program comprised three modules over 5 weeks and a preassessment examination. Premodule 1 imparted cognitive skills; Module 1 was on structured wet-lab, Module 2 was about phacoemulsification step surgery, and Module 3 had independent complete surgeries. Group 2 also underwent compulsory Observation of cases being performed in the operation theater, surgical video recording review, and formative feedback. Mean OSCAR score comparison was done for both the groups. The OSCAR score was also calculated case-wise to obtain the learning curve with respect to the entry and exit levels, by classifying the trainees in each group as Novice, Beginner, Advanced Beginner, or Competent. A comparison of the posterior capsular rupture (PCR) rates and vision at discharge of all the cases was done. Results: Group 2 had a significantly better mean OSCAR score than Group 1 (4.03 and 3.43, respectively; P < 0.001). The PCR rate of the cases was significantly lower in Group 2 than in Group 1 (9.14% and 20.30%, respectively; P < 0.001). Group 2 had a significantly better visual acuity outcome of the cases than Group 1. Group 1 started as Novice (OSCAR score: 2), whereas Group 2 started as Beginner (OSCAR score: 3). Group 2 reached the Advanced Beginner level eight to 10 cases prior to Group 1. Conclusion: A structured training curriculum can make a significant difference in the training experience of the trainees and enable better surgical outcomes and a decrease in the complication rates.